Probiotic administration correlated with reduced diarrheal incidence and improved gut microbiota diversity in young goats - Essa, Mohamed Osman Abdalrahem; Cheng, Cheng; Li, Jun; Han, Xiao; Wei, Zhong Kang; Abdelhadi, Layla Ahmed Mohammed; Hassan, Huda Ahmed; Adam, Saber Y.; Husien, Hosameldeen Mohamed; Saleh, Ahmed A.; Cheng, Darong (Frontiers in Veterinary Science, 2025)
IntroductionProbiotic interventions in young livestock are gaining attention for their potential health benefits.MethodsThis study involved 15 weaned goat kids (2–3 months old; 10–15 kg body weight), including 10 healthy kids and 5 diarrheic kids. The kids were divided into three groups: Healthy Control (H, no treatment), Probiotic-Treated Healthy (T), and Diarrheic + Probiotic-Treated (D). All kids were maintained under standardized environmental conditions and fed a controlled diet (60% corn, 15% pea skin, 15% silage, 5% hay and 1% vitamin-mineral additives). Probiotic bacteria Enterococcus faecium and Bacteroides fragilis were administered via oral gavage at a concentration of (1 × 109) CFU/mL for five consecutive days. Fecal samples were collected for sequencing of the bacterial 16S rRNA gene to analyze microbial composition.ResultsHealthy groups exhibited significantly greater species richness and diversity compared to the diarrheal group (p < 0.01). The predominant phyla identified were Pseudomonadota, Bacteroidetes, and Bacillota.Increased levels of Xylanibacter, UCG-055, Bacteroides, and Escherichia-Shigella were noted in healthy treated kids, while Prevotellaceae UG_001 and Proteus decreased.DiscussionThe findings highlight significant gut microbiota differences between healthy and diarrheal kids, suggesting that modifications in gut microbiota composition could alleviate diarrhea, contributing to preventive and therapeutic strategies for this condition.